2020
DOI: 10.1371/journal.pgen.1008837
|View full text |Cite
|
Sign up to set email alerts
|

Control of mRNA translation by dynamic ribosome modification

Abstract: Control of mRNA translation is a crucial regulatory mechanism used by bacteria to respond to their environment. In the soil bacterium Pseudomonas fluorescens, RimK modifies the Cterminus of ribosomal protein RpsF to influence important aspects of rhizosphere colonisation through proteome remodelling. In this study, we show that RimK activity is itself under complex, multifactorial control by the co-transcribed phosphodiesterase trigger enzyme (RimA) and a polyglutamate-specific protease (RimB). Furthermore, bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…Hfq controls multiple phenotypes in SBW25 (7), however the effects of Hfq dysregulation upon rsmQ deletion appeared to be modest, particularly when compared to secondary Hfq control by the RimABK system, for example (7,78). An intriguing possibility is that the plasmid-borne Hfq homologue pQBR0137, whose abundance increases in the absence of rsmQ, may compensate for reduced chromosomal Hfq activity.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Hfq controls multiple phenotypes in SBW25 (7), however the effects of Hfq dysregulation upon rsmQ deletion appeared to be modest, particularly when compared to secondary Hfq control by the RimABK system, for example (7,78). An intriguing possibility is that the plasmid-borne Hfq homologue pQBR0137, whose abundance increases in the absence of rsmQ, may compensate for reduced chromosomal Hfq activity.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of multiple, interconnected layers of regulation make signalling phenotypes challenging to interrogate in a laboratory setting. For example, Hfq is global master regulator of translation (7,55) and has an overlapping regulon with the Rsm proteins (76) as well as circumstances in which Hfq and RsmA directly interact (77), adding further regulatory complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RimK is, intriguingly, an ATP-dependent glutamate ligase (Kang et al, 1989) that can append glutamate residues to the C-terminus of protein S6 (RpsF) located in the ribosomal 30S subunit (Zhao G. et al, 2013). By regulating the function of the posttranslational modification of ribosomal protein RpsF, RimK can control the translation of some relevant proteins (Kino et al, 2011;Grenga et al, 2020). Studies have shown that RimA, RimB and c-di-GMP can all activate RimK (Figure 4C).…”
Section: Indirect Regulation Between Hfq and C-di-gmpmentioning
confidence: 99%
“…RimB ensures that glutamate chains on RpsF are formed in units of four. All three proteins interact, and their function maintains a fine balance of translational control in response to low temperature, nutrient deprivation and c-di-GMP concentration, which are known to regulate expression of the operon [15].…”
Section: Gene Regulation and Signallingmentioning
confidence: 99%